2023
DOI: 10.20517/cs.2022.33
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nanomaterials enabled flexible and wearable electronics

Abstract: Selenium (Se), as an intriguing chalcogenide semiconductor, has traditionally been used for solar energy harvesting. The recent development of nanoscience and nanotechnology has enabled a myriad of Se nanomaterials with compelling structures and unique features. Compared with other chalcogens, Se nanomaterials possess anisotropic crystalline structure, intrinsic chirality, and high reactivity, as well as unique optical, electrical, photoconductive, and piezoelectrical properties. The integration of these Se na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Moreover, these materials exhibit exceptional physicochemical properties. The incorporation of selenium (Se) nanoparticles into materials of technical importance, such as conductors and semiconductors, on substrate that is plastic, bendy, stretchable, and extremely curved, represents a significant and advanced development in the realm of flexible and wearable electronics utilizing Se nanomaterials [20]. Recent research has also indicated the significant potential of selenium nanoparticles in serving as great performances electrode for energy storing device.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these materials exhibit exceptional physicochemical properties. The incorporation of selenium (Se) nanoparticles into materials of technical importance, such as conductors and semiconductors, on substrate that is plastic, bendy, stretchable, and extremely curved, represents a significant and advanced development in the realm of flexible and wearable electronics utilizing Se nanomaterials [20]. Recent research has also indicated the significant potential of selenium nanoparticles in serving as great performances electrode for energy storing device.…”
Section: Introductionmentioning
confidence: 99%
“…Prof. Stefano A. Cerri from Italy contributed a paper entitled "Information, knowledge, and human learning for chemistry: the visionary contribution of Professor Alain Krief" [7] . We are deeply grateful to Prof. Vivian Wing-Wah Yam, the current and first female president of the IOCD, for her excellent contribution entitled "Luminescent alkynylplatinum(II) terpyridine-containing conjugated polymers: synthesis, characterization and photophysical studies" [8] . The excellent review paper from Prof. Wei Yan from Singapore and China on "Selenium nanomaterials enabled flexible and wearable electronics" [9] is highly appreciated.…”
mentioning
confidence: 99%